Plasticity of repetitive sequences demonstrated by the complete mitochondrial genome of Eucalyptus camaldulensis - Fukasawa, Yoshinori; Driguez, Patrick; Bougouffa, Salim; Carty, Karen; Putra, Alexander; Cheung, Ming-Sin; Ermini, Luca (Frontiers in Plant Science, 2024)
The tree, Eucalyptus camaldulensis, is a ubiquitous member of the Eucalyptus genus, which includes several hundred species. Despite the extensive sequencing and assembly of nuclear genomes from various eucalypts, the genus has only one fully annotated and complete mitochondrial genome (mitogenome). Plant mitochondria are characterized by dynamic genomic rearrangements, facilitated by repeat content, a feature that has hindered the assembly of plant mitogenomes. This complexity is evident in the paucity of available mitogenomes. This study, to the best of our knowledge, presents the first E. camaldulensis mitogenome. Our findings suggest the presence of multiple isomeric forms of the E. camaldulensis mitogenome and provide novel insights into minor rearrangements triggered by nested repeat sequences. Comparative sequence analysis of the E. camaldulensis and E. grandis mitogenomes unveils evolutionary changes between the two genomes. A significant divergence is the evolution of a large repeat sequence, which may have contributed to the differences observed between the two genomes. The largest repeat sequences in the E. camaldulensis mitogenome align well with significant yet unexplained structural variations in the E. grandis mitogenome, highlighting the adaptability of repeat sequences in plant mitogenomes.